2019
DOI: 10.1108/jsm-10-2018-0304
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: transformative service research and social marketing – converging pathways to social change

Abstract: Purpose The purpose of this paper is to discuss two parallel but distinct subfields of marketing that share common interests (enhancing consumers’ lives and improving well-being): social marketing and transformative service research. The authors also suggest a research agenda. Design/methodology/approach The paper offers a conceptual approach and research agenda by comparing and contrasting the two marketing fields of transformative service research and social marketing. Findings Specifically, this paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 54 publications
3
99
0
Order By: Relevance
“…By contrast, sectors that seek profit maximisation (e.g., the financial sector) may achieve long-term sustainable goals through recognising system wellbeing needs through a holistic emphasis, as opposed to overemphasising macro-level domains (e.g., strategic well-being) that may result in value destruction. These implications are consequential to improving quality of life and is particularly relevant to achieving social change (Russell-Bennett et al, 2019), since a systems perspective allows for a more strategic approach (French and Gordon, 2019).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…By contrast, sectors that seek profit maximisation (e.g., the financial sector) may achieve long-term sustainable goals through recognising system wellbeing needs through a holistic emphasis, as opposed to overemphasising macro-level domains (e.g., strategic well-being) that may result in value destruction. These implications are consequential to improving quality of life and is particularly relevant to achieving social change (Russell-Bennett et al, 2019), since a systems perspective allows for a more strategic approach (French and Gordon, 2019).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…There is a relatively established line of sport management research investigating topics related to the relationship between sport services and well-being (e.g., Dixon & Warner, 2010;Inoue, Sato, Filo, Du, & Funk, 2017;Jang, Ko, Wann, & Kim, 2017;Kim, Kim, Newman, Ferris, & Perrewé, 2019;Sato, Jordan, & Funk, 2015;Westberg & Kelly, 2019). However, due to the absence of a coordinated effort to synthesize this line of research, it has not reached its full potential to make a distinctive contribution, as indicated by a lack of reference to sport services in the broader transformative service research literature (Alkire et al, 2019;Anderson & Ostrom, 2015;Russell-Bennett, Fisk, Rosenbaum, & Zainuddin, 2019). By introducing the terminology of TSSR and displaying high-quality TSSR scholarship through the flagship sport management journal, we have aimed to provide an overarching framework for this research area and to facilitate coordination to produce knowledge that is highly impactful within and beyond the sport management literature.…”
mentioning
confidence: 99%
“…The authors pursue an interdisciplinary approach to propose a theoretical framework for sustaining a wellbeing advantage in the healthcare context. In line with Russell-Bennett et al ( 2019 ) proposals, this study propels both TSR and social marketing forward: adopting more customer-oriented approaches; and taking a non-linear approach to theory development that innovates and co-creates solutions. By attending to the research agenda forwarded within TSR and applying SD and CD logics, this paper initiates academic discussion of the connection of CPSW with TSD, suggests implications for marketers, and proposes avenues for future research.…”
Section: Discussionmentioning
confidence: 73%